Immune Reconstitution Profiling Suggests Antiviral Protection after Transplantation with Omidubicel: A Phase 3 Substudy - Paul Szabolcs; Roei D. Mazor; Dima Yackoubov; Stuart B. Levy; Patrick J. Stiff; Andrew R. Rezvani; Rabi Hanna; John E. Wagner; Amy K. Keating; Caroline A. Lindemans; Nicole Karras; Joseph P. McGuirk; et al. (2023)
Allogeneic hematopoietic cell transplantation (HCT) is a potentially curative treatment for hematologic malignancies and nonmalignant disorders. Rapid immune reconstitution (IR) following allogeneic HCT has been shown to be associated with improved clinical outcomes and lower infection rates. A global phase 3 trial (ClinicalTrials.gov NCT02730299) of omidubicel, an advanced cell therapy manufactured from an appropriately HLA-matched single umbilical cord blood (UCB) unit, showed faster hematopoietic recovery, reduced rates of infection, and shorter hospitalizations in patients randomized to omidubicel compared with those randomized to standard UCB. This optional, prospective substudy of the global phase 3 trial characterized the IR kinetics following HCT with omidubicel compared with UCB in a systematic and detailed manner. This substudy included 37 patients from 14 global sites (omidubicel, n = 17; UCB, n = 20). Peripheral blood samples were collected at 10 predefined time points from 7 to 365 days post-HCT. Flow cytometry immunophenotyping, T cell receptor excision circle quantification, and T cell receptor sequencing were used to evaluate the longitudinal IR kinetics post-transplantation and their association with clinical outcomes. Patient characteristics in the 2 comparator cohorts were overall statistically similar except for age and total body irradiation (TBI)-based conditioning regimens. The median patient age was 30 years (range, 13 to 62 years) for recipients of omidubicel and 43 years (range, 19 to 55 years) for UCB recipients. A TBI-based conditioning regimen was used in 47% of omidubicel recipients and in 70% of UCB recipients. Graft characteristics differed in their cellular composition. Omidubicel recipients received a 33-fold higher median dose of CD34+ stem cells and one-third of the median CD3+ lymphocyte dose infused to UCB recipients. Compared with UCB recipients, omidubicel recipients exhibited faster IR of all measured lymphoid and myelomonocytic subpopulations, predominantly in the first 14 days post-transplantation. This effect involved circulating natural killer (NK) cells, helper T (Th) cells, monocytes, and dendritic cells, with superior long-term B cell recovery from day +28. At 1 week post-HCT, omidubicel recipients exhibited 4.1- and 7.7 -fold increases in the median Th cell and NK cell counts, respectively, compared to UCB recipients. By 3 weeks post-HCT, omidubicel recipients were 3-fold more likely to achieve clinically relevant Th cell and NK cell counts ≥100 cells/µL. Similar to UCB, omidubicel yielded a balanced cellular subpopulation composition and diverse T cell receptor repertoire in both the short term and the long term. Omidubicel's CD34+ cell content correlated with faster IR by day +7 post-HCT, which in turn coincided with earlier hematopoietic recovery. Finally, early NK and Th cell reconstitution correlated with a decreased rate of post-HCT viral infections, suggesting a plausible explanation for this phenomenon among omidubicel recipients in the phase 3 study. Our findings suggest that omidubicel efficiently promotes IR across multiple immune cells, including CD4+ T cells, B cells, NK cells, and dendritic cell subtypes as early as 7 days post-transplantation, potentially endowing recipients of omidubicel with early protective immunity.